HIERARCHIES OF CONSCIOUSNESS AND THE PRINCIPLE OF UNITY: RELIGION AT STAKE - Axinciuc, Madeea (European Scientific Journal, ESJ, 2013)
Recent research in the integrative area of consciousness studies mainly focused on the mind & body interaction, exploiting tools, methods and contents particular to natural sciences or cognitive studies. The resources available in the multidisciplinary field of religious studies are still precariously utilized. New research methodologies are to be configured in order to integrate the contribution of the religious studies area to the understanding of the phenomenology of the mind. The present study revisits, in this new light, the key-concepts of ‘sacred’, ‘ultimate principle’ and ‘hierarchy’ as theorized in philosophy of religion and comparative religion, aiming at highlighting the possible elements and triggers which might re-orientate the applied study of religion toward the exploration of human mind and its apprehension of reality. The assumption is that there is a link between different states of consciousness and different levels of reality, described or envisaged in the religious discourse as ‘divine hierarchy.’